Profiling kinetics and kinematics of collegiate volleyball players based on position group and division - Richards, P.; Handy, R.; Reyes, C. (International Journal of Exercise Science Conference Proceedings, 2025)
The countermovement jump (CMJ) is an athletic test that can be used to derive meaningful metrics to assess player performance, especially in volleyball. This data can be used to inform player differences in relation to position, divisions, and overall movement strategies. PURPOSE: To profile CMJ kinetics and kinematics of NCAA volleyball players based on position, as well as to compare D3 CMJ metrics to DI. METHODS: NCAA D3 and D1 women`s volleyball players (n = 99, 23 + 2.3 years, 175.4 + 8.4 cm, 71.3 kg + 11.7) completed 3 maximal effort CMJs on force plates during their preseason testing. The participants` highest jump height (JH) of their 3 trials, and its corresponding 6 kinetic metrics, were used in the analyses. ANOVAs were conducted to compare jump metrics across positions and level of play with the alpha being set to p < 0.05. A Bonferroni post-hoc analysis was used to identify specific statistical differences between jump metrics, positions, and level of play. RESULTS: Significant differences resulted in Right Side Hitters creating higher braking rate of force development (BRFD) than Defensive Specialists (p < 0.005), and both Right Side Hitters and Middle Blockers displayed greater peak propulsive force (PPF) than Defensive Specialists (p < 0.005). Between divisions, D1 athletes exhibited significantly higher jump height (JH) compared to D3 athletes (p < 0.005). D1 athletes achieved higher JH due to deeper countermovement depth (CMD), higher reactive strength index-modified (mRSI), higher peak PPF, and greater relative propulsive impulse (RPI) (p < 0.005). CONCLUSION: Significant positional differences in jump strategy were presented, particularly for defensive specialists. When compared level of play, D1 volleyball players displayed greater values across multiple CMJ metrics, meaning they have enhanced neuromuscular abilities than D3. The jump data has implications for profiling, recruiting, and training adaptations. Future research should expand participant age, gender, include other divisions of play, and compare volleyball athletes to other sports.